2004
DOI: 10.1093/humrep/deh449
|View full text |Cite
|
Sign up to set email alerts
|

Late paternity and stillbirth risk

Abstract: The effect of paternal ageing on stillbirth risk is revealed in mothers aged > or =30 years and is modified by family education. In mothers aged 30-34 years from families with high education, the increase imputable to paternal ageing might be indicative of a genetic component.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 39 publications
3
25
0
2
Order By: Relevance
“…We found that paternal age was an independent risk factor for adverse fetal birth outcomes, in which elevated risks for stillbirth and late stillbirth were observed for the older paternal age categories. These findings support the current hypothesis that in utero fetal development and survival are influenced by not only maternal but also paternal characteristics and is supported by previous research on paternal aging and stillbirth risk (Astolfi et al, 2004). Furthermore, the findings of this study are congruent with the notion of including fathers within the current framework of prenatal care and decision making, as well as counseling during the preconception period, to optimize pregnancy outcomes.…”
Section: Discussionsupporting
confidence: 90%
“…We found that paternal age was an independent risk factor for adverse fetal birth outcomes, in which elevated risks for stillbirth and late stillbirth were observed for the older paternal age categories. These findings support the current hypothesis that in utero fetal development and survival are influenced by not only maternal but also paternal characteristics and is supported by previous research on paternal aging and stillbirth risk (Astolfi et al, 2004). Furthermore, the findings of this study are congruent with the notion of including fathers within the current framework of prenatal care and decision making, as well as counseling during the preconception period, to optimize pregnancy outcomes.…”
Section: Discussionsupporting
confidence: 90%
“…In Spain registration of foetal deaths is required only in cases where the gestation is greater than 180 days. This threshold is comparable to the Italian ISTAT definition (Astolfi et al 2004). Huang et al (2008) suggested that, in the absence of pre-existing medical disorders, it is difficult to establish a range of limit points within a continuous variable, such as age.…”
Section: Introductionmentioning
confidence: 53%
“…Growing evidence indicates that paternal aging is also a risk factor for congenital malformations and genetic disorders (Newcombe and Tavendale, 1965;Savitz et al, 1991;Crow, 2000;Zhu et al, 2008), which may be linked to accumulation of mutations in germ cells of aging parents, perhaps resulting from normal wear and tear as well as exposure to harmful environments over time (Savitz et al, 1991;Yauk et al, 2007;Malik et al, 2008). Moreover, child bearing at a later age is associated with adverse birth outcomes, such as preeclampsia, pre-term birth, stillbirth, low birthweight and child mortality; and predisposition of the offspring to serious health problems such as autism, epilepsy, schizophrenia and Alzheimer's disease (Fretts et al, 1995;Bertram et al, 1998;Abel et al, 2002;Harlap et al, 2002;Byrne et al, 2003;Astolfi et al, 2004Astolfi et al, , 2006Vestergaard et al, 2005;Durkin et al, 2008;Zhu et al, 2008). Advanced maternal age at childbirth has been linked to menstrual disorders and subfecundity in daughters owing to endocrinological irregularities (Smits et al, 1997).…”
Section: Introductionmentioning
confidence: 99%